Seeing The Sacred: Myth, Materiality, And Narratives Of Indigenous Asante Shrine Murals - Jectey-Nyarko , Mantey; Opoku-Bonsu, Kwame; Quarshie, Benjamin; Annor Anim, Felix (Lembaga Penelitian Universitas Pasundan, 2025)
Murals, usually seen as decorations on walls have didactic, aesthetic, and spiritual connotations. Historically, they have been done for aesthetic and documentation of cultural practices and philosophies of the recipient culture. They are also used for rituals and to keep records of the cultural environment across time as evident in images found in ancestral caves and rock representations. The Asante of Ghana is known for elaborate indigenous architecture with abstract and culturally embedded imagery. most of these architectures, which were part of the heritage of the Asante Kingdom, have been lost to war and time. Some surviving indigenous architecture with remarkable murals in Asante includes shrine houses and a few ancient palaces, which have been designated as world heritage sites. With the advent of modern public and domestic architecture and the redesigning of Kumasi into a British Colonial “Garden City”, these decorations are not just fading away but losing their cultural essence. The study used a qualitative phenomenology and a narratological approach to source primary data from participants in six selected Indigenous communities of Asante through purposive and simple random sampling. The study unearthed the spiritual essence and philosophies of the Asante shrine murals embedded in the people’s traditional symbols and proverbial sayings as a way of maintaining their unique identity as its main findings. Authors thus recommend the incorporation of such traditional symbols, especially the endangered/extinct ones into modern architectural designs and mural representations to reinforce history and cultural identity.